1992
DOI: 10.1111/j.1748-1716.1992.tb09400.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prostaglandins and a prostaglandin H synthase inhibitor on cervical secretion of the guinea‐pig

Abstract: The modulatory effects of several prostaglandins and a prostaglandin H synthase inhibitor (indomethacin) on basal as well as nerve stimulation induced secretion from the cervical glands of the guinea-pig were studied. Hypogastric nerve stimulation resulted in a secretory response of +113%. Indomethacin dose dependently inhibited this secretory response. Prostaglandins E2, F2 alpha and I2 inhibited and 19-OH prostaglandin E1 reduced nerve stimulation induced secretion. Prostaglandin I2 and 19-OH PGE1 markedly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Moreover, a noradrenergic, non‐cholinergic innervation has been suggested and several local transmitters and modulators have been suggested – e.g. adenosine, prostaglandins, and NO – among others (4–7). The secretory response of the uterine linings to the muscarinic drug carbachol is in accordance with previous studies on uterine secretion at ovulation and implantation time (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a noradrenergic, non‐cholinergic innervation has been suggested and several local transmitters and modulators have been suggested – e.g. adenosine, prostaglandins, and NO – among others (4–7). The secretory response of the uterine linings to the muscarinic drug carbachol is in accordance with previous studies on uterine secretion at ovulation and implantation time (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Priming with female sex hormones is necessary to elicit the cholinergic secretory response (4,5). A non‐adrenergic, non‐cholinergic innervation has also been suggested and adenosine analogs as well as prostaglandins have been shown to modulate guinea pig endometrial secretion (6,7). It has further been suggested that nitric oxide (NO) production is a prerequisite for the muscarinic secretory response in the endometrium at ovulation time and also in other neurogenic‐influenced secretory processes, such as cervical secretion, at ovulation.…”
mentioning
confidence: 99%
“…It is agreed that prostaglandin inhibitors may reduce cervical secretion (20). An influence of the female sex hormone is also plausible because in the rat uterus and cervix NO is produced mainly by the cytokine‐inducible NO synthase, which is progesterone dependent (20, 21). We can only speculate on the importance of modulatory effects in terms of interactions with the NO second messenger system and/or the autonomic nervous system, as regards fertility and fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…The character of the mucus is mainly due to the mucin, rich in mucopolysaccharides and produced by the secretory glandular cells. At a central as well as a peripheral level, the cervical secretion can be modulated by the nervous system (3,4). The glands of the uterine linings of the guinea pig possess a sympathetic cholinergic secretomotor innervation and muscarinic receptor stimulation releases preformed mucin.…”
mentioning
confidence: 99%
“…In a study in humans (7), it was demonstrated that cervical secretion could be inhibited by atropine and increased by the cholinomimetic drug carbacholine, thus suggesting a cholinergic secretomotor innervation of cervical glands. Prostaglandin synthase inhibitors can reduce uterine and cervical secretion at ovulation time in the guinea pig (3). Also in humans, a reduction of cervical secretion after administration of indomethacin can be seen (7).…”
mentioning
confidence: 99%